2013
DOI: 10.1016/j.devcel.2012.12.016
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-92a Upholds Bmp Signaling by Targeting noggin3 during Pharyngeal Cartilage Formation

Abstract: Craniofacial malformations are common structural birth defects and usually associate with abnormal development of pharyngeal arches. Although some microRNAs have been found to be implicated in chondrogenesis in vitro, few have been shown to be essential for cartilage and bone development at the whole organism level. In this study, we report that mir92a is highly enriched in the chondrogenic progenitors and that its inactivation results in loss of pharyngeal cartilage elements due to poor proliferation, impaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
82
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 73 publications
5
82
1
Order By: Relevance
“…Ning et al [40] demonstrated a positive effect of miR-92a on the proliferation, differentiation, and survival of chondrogenic progenitor cells by targeting nog3, an inhibitor of the BMP signaling pathway. MiR-92a expression decreases rapidly in macrophages upon stimulation with Toll-like receptor ligands, and miR-92a controls the inflammatory response by targeting the MKK4/JNK/c-Jun pathway [41].…”
Section: Discussionmentioning
confidence: 99%
“…Ning et al [40] demonstrated a positive effect of miR-92a on the proliferation, differentiation, and survival of chondrogenic progenitor cells by targeting nog3, an inhibitor of the BMP signaling pathway. MiR-92a expression decreases rapidly in macrophages upon stimulation with Toll-like receptor ligands, and miR-92a controls the inflammatory response by targeting the MKK4/JNK/c-Jun pathway [41].…”
Section: Discussionmentioning
confidence: 99%
“…Particularly p63 might be interesting, because mutations in humans cause skeletal syndromes with digit abnormalities [22] and its overexpression in mice induced accelerated ossifications in long bone digits and tail bones [23]. Moreover, inactivation of miR-92a in zebrafish increased noggin3 expression leading to an inhibition of Bmp signaling and abnormal behavior of chondrogenic progenitors during pharyngeal cartilage formation [24].…”
Section: Discussionmentioning
confidence: 99%
“…Microinjection and whole-mount in situ hybridization were performed as before [7881]. Apoptosis were determined by TUNEL assay [82]. WT and p53 mutant zebrafish embryos were injected with object mRNA at one-cell stage and then harvested at 24 hpf for TUNEL labeling using In Situ Cell Death Detection Kit, TMR red (12156792910, Roche) according to the manufacturer’s instruction.…”
Section: Methodsmentioning
confidence: 99%